Influence of Different Extraction Methods on Fatty Acid Composition of Lipid Extracts of Chlorella vulgaris Beijerinck from Laguna De Bay, Philippines - Saracanlao, Rochelle Joie A.; Nacorda, June Owen O.; Hernandez, Hidelisa P. (2019)
Chlorella vulgaris Beijirinck cultures isolated from Laguna de Bay were cultivated and the biomass produced after one month of cultivation was subjected to stepwise selection of solvent system, algae-to-solvent ratio, and extraction method. The optimized procedure for C. vulgaris was found to be sonication with 2:1 (v:v) chloroform:methanol as extractant at 1:20 (g:ml) algae:solvent ratio producing 51% crude lipid (dry-weight basis). Using thin layer chromatography, the C. vulgaris lipid extract showed the following approximate composition: triglycerides (79%), sterols (14%), and 1,3-diglycerides present in substantial amounts. Gas chromatography – flame ionization detection of the fatty acids as fatty acid methyl esters showed the following components: myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, and traces of lauric acid. Analysis of the lipid extracts showed that extraction procedure, along with the solvent system, affects both yield and lipid profile. Total lipid yield and sterol yield increase with increasing polarity of the solvent system. Triglycerides, on the other hand, decreases with the polarity of solvent systems used. A more varied fatty acid class was obtained using more polar solvents (8 fatty acids) compared with the usage of less polar ones (1–3 fatty acids).
Keywords: Fatty acid; Microalgae